1983
DOI: 10.2307/3281241
|View full text |Cite
|
Sign up to set email alerts
|

Pathology (?) of Plagiorhynchus cylindraceus in the Starling, Sturnus vulgaris

Abstract: Our field study did not support anecdotal claims alleging pathogenicity on the part of P. cylindraceus in starlings. Within-clutch analysis of nestling starling weights (n = 25) over time showed that P. cylindraceus had no effect on position in clutch relative to siblings. Parasitized nestlings tended to weigh more than control siblings. Within-sex analysis of wild adult starling weight (n = 103) showed no difference between animals with acanthocephalans and uninfected animals and weight was not related to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Furthermore, damage to the intestinal mucosa caused by the parasites may interfere with absorption of dietary nutrients. Histopathological lesions associated with acanthocephalans have been reported in the intestines of wild birds (Thompson-Cowley et al, 1979;Moore and Bell, 1983;McOrist and Scott, 1989), and the inflammatory response found in eider ducklings was similar to that earlier described in other birds. The reaction consisted of local infiltrations of mixed inflammatory cells and was restricted to the mucosal layer of the small intestine.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, damage to the intestinal mucosa caused by the parasites may interfere with absorption of dietary nutrients. Histopathological lesions associated with acanthocephalans have been reported in the intestines of wild birds (Thompson-Cowley et al, 1979;Moore and Bell, 1983;McOrist and Scott, 1989), and the inflammatory response found in eider ducklings was similar to that earlier described in other birds. The reaction consisted of local infiltrations of mixed inflammatory cells and was restricted to the mucosal layer of the small intestine.…”
Section: Discussionsupporting
confidence: 61%
“…basal metabolism, activity, thermoregulation, growth, reproduction etc.) in a form directly transferable from the level of the individual to that of the host's population (Robbins, 1983 (Schmidt, 1963;Holloway, 1966;ThompsonCowley et al 1979;Moore & Bell, 1983). The purpose of this study was to determine if, under either stressed or unstressed thermal conditions, initial infection with P. cylindraceus measurably affects energy consumption and use in a definitive host, the European starling (Sturnus vulgaris).…”
Section: Introductionmentioning
confidence: 98%
“…Recently Wanstall et al (1986) reported electron microscopical results on Pomphorhynchus laevisin experimentally infected rainbow trout. Investigations on acanthocephalan histopathology in birds (Pflugfelder 1956, Moore & Bell 1983 and mammals (Chandler 1953, Takos & Thomas 1958, Richart & Benirschke 1963, Moore 1979, Tesana et al 1982, Leng et al 1983, Nelson & Nick01 1986) have also been O Inter-Research/Printed in F. R. Germany mainly confined to light microscopical studies except for a scanning electron microscopical examination of the rat intestine experimentally infected with Moniliforrnis rnoniliformis (Martin et al 1983).…”
Section: Introductionmentioning
confidence: 99%